Studi Performa Turbin Angin Sumbu Vertikal NACA 0012 Dengan Turbin Angin DARRIEUS-H Pada Variasi Sudut Pitch 35 Derajat,40 Derajat,45 Derajat,50 Derajat,55 Derajat,60 Derajat - Safi'i, H'mim; , Nur Akhlis, ST,. MT; , Ir. Tri Tjahjono, MT (2016)
The more expensive and the more limited fossil energy resaourch as the electricity power, and the increase of awarness to preserve the environmental condition, therefore, alternativ energy resourch is necessary to be taken. Wind is a kind of renewal energy which is environmentaly friendly. Wind energy can be aplied by using wind turbine. The kind of wind turbine used in the final report research is Darrieus type-H wind turbine with aerofoil NACA 0012, the cord long is 0,3 m. The wind turbin dimension is (D) 0,44 m, tall (H) 0,6 m. The pitch degree variations done in this research test are (350, 400, 450, 500, 550, 600). The purpose of this research was to find out find out the relationship of pitch degree toward the Darrieus-H turbine performance. The research was done by using wind tunnel with the wind velocity of 4,8 m/s. The result obtained from the test indicated that the wind turbine with pitch degree of 550 is more effective to ekstract the wind energy, and each effeciency of the degree of 350, 400, 450, 500, 550, 600 are 4,11%, 4,16%, 4,39%, 4,51%, 4,62%, 4,16%. Keywords : Darrieus-H Wind Turbine, NACA 0012, Pitch Degree, Effeciency